An evaluation of factors associated with completion and benefit from pulmonary rehabilitation in COPD. Issue 1 (3rd November 2014) - Boutou, Afroditi K; Tanner, Rebecca J; Lord, Victoria M; Hogg, Lauren; Nolan, Jane; Jefford, Helen; Corner, Evelyn J; Falzon, Christine; Lee, Cassandra; Garrod, Rachel; Polkey, Michael I; Hopkinson, Nicholas S
Abstract : Background: Pulmonary Rehabilitation (PR) is an important treatment for patients with chronic obstructive pulmonary disease (COPD) but it is not established whether any baseline parameter can predict response or compliance. Aim: To identify whether baseline measures can predict who will complete the programme and who will achieve a clinically significant benefit from a Minimum Clinical Important Difference (MCID) in terms of exercise capacity and health-related quality of life (HRQoL). Methods: Data were collected prospectively from patients with COPD at their baseline assessment for an outpatient PR programme in one of eight centres across London. 'Completion' was defined as attending at least 75% of the designated PR visits and return for the follow-up evaluation. The MCID for outcome measures was based on published data. Results: 787 outpatients with COPD (68.1±10.5 years old; 49.6% males) were included. Patients who completed PR (n=449, 57.1%) were significantly older with less severe airflow obstruction, lower anxiety and depression scores, less dyspnoea and better HRQoL. Only baseline CAT score (OR=0.925; 95% CI 0.879 to 0.974; p=0.003) was retained in multivariate analysis. Patients with the lowest baseline walking distance were most likely to achieve the MCID for exercise capacity. No baseline variable could independently predict achievement of an MCID in HRQoL. Conclusions: Patients with better HRQoL are more likely to complete PR while worse baseline exercise performance makes the achievement of a positive MCID in exercise capacity more likely. However, no baseline parameter could predict who would benefit the most in terms of HRQoL.